EFL Students’ Difficulties on Using Subject-Verb Agreement - Amara Aulia Putri; Erni Sukesi; Zahrida (UNIB Press, 2023)
The purpose of this study is to determine the common subject-verb agreement difficulties that students encounter in the English Education Study Program at the University of Bengkulu. This study adopted a qualitative methodology. The population was the sixth semester of the 2022/2023 a English Education Study Program. The sample of this study was 33 students consisting of 11 males and 22 females. Data collection was done through validated and reliable tests consisting of 30 items representing 6 subject-verb agreements; full verbs, linking verbs, modals, auxiliary be, auxiliary have, and auxiliary do. Furthermore, this study used simple statistics (percentage and average) to analyze the data. In accordance to the study's findings, the majority of learners have struggles using subject-verb agreements. Found 540 obstacles in the test. The students' own difficulties were difficulties using Full Verbs (18%), Linking Verbs (21.5%), Modals (23%), Auxiliary be (16.5%), Auxiliary have (14%), and Auxiliary do (7%). Modal becomes the dominant difficulty for students. It was possible that students have difficulty understanding patterns in modals and did not know the term modals themselves. Moreover, students also could not identify the subject and verb in the sentence, lacked vocabulary, did not practice often, and did not recheck wrong answers. This result suggests that an appropriate method is still needed to improve understanding with subject-verb agreement.